Making Room for People Choice, Voice and Liveability in Residential Areas - Qu, Lei (Techne Press, 2011)
Making Room for People elaborates on preferences in housing. It explores how users, occupants, and citizens can express their needs, searching for the enhancement of individual choice and control over their residential environment, and the predicted positive spin-off's for urban collectives. The central question is: What are the conditions under which an increase of people's choice and voice over the places they inhabit contribute to more liveable urban areas? The options to make choices and to have a say in urban design and housing matters are used as a conceptual framework. 'Choice' and 'voice' are the main concepts that structure the empirical material.